2010 22nd International Conference on Indium Phosphide and Related Materials (IPRM) 2010
DOI: 10.1109/iciprm.2010.5516289
|View full text |Cite
|
Sign up to set email alerts
|

TM mode waveguide isolator monolithically integrated with InP active devices

Abstract: We propose and experimentally demonstrate a novel structure for monolithically integrating a TMmode waveguide optical isolator with active InP devices. A semiconductor ring laser with integrated isolator is fabricated and demonstrated for the first time.I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Reduced threshold current and enhanced modal gain also contribute to larger extinction ratio in magnetically controllable nonreciprocal semiconductor lasers owing to the Fabry-Perot resonance effect, and in unidirectional ring lasers owing to the resonant ring cavity effect. 28) Fig. 2.…”
Section: Layer Structure Design Of Nonreciprocal Semiconductor Lasermentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced threshold current and enhanced modal gain also contribute to larger extinction ratio in magnetically controllable nonreciprocal semiconductor lasers owing to the Fabry-Perot resonance effect, and in unidirectional ring lasers owing to the resonant ring cavity effect. 28) Fig. 2.…”
Section: Layer Structure Design Of Nonreciprocal Semiconductor Lasermentioning
confidence: 99%
“…27) Unidirectional semiconductor ring lasers (SRLs) utilizing nonreciprocal semiconductor lasers have been realized. 26,28,29) Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) The extinction ratio of 14.7 dB/mm corresponds to 0.147 dB/10 m, which is sufficient for realizing unidirectional lasing. 17) In summary, we have reported on the photon density redistribution in nonreciprocal semiconductor optical amplifiers. The fabricated nonreciprocal semiconductor optical amplifiers exhibited Fabry-Perot lasing whose intensity was modulated by the magnetization direction, and the extinction ratio was 1.9 dB.…”
mentioning
confidence: 94%
“…The ring radius and length of the semiconductor optical isolator are both 500 µm, and the threshold current is 170 mA. 32) It was reported that the amount of optical isolation for TM-mode unidirectional ring lasing is 0.5 dB in the ring cavity with a Y-branch coupler, on the basis of an analysis using Lamb equations in the ring cavity. 33) We have analyzed the amount of optical isolation for TE-mode unidirectional lasing in the ring cavity composed of ring radius r = 100 µm, a 120-µm-long semiconductor optical amplifier, and an 80-µm-long semiconductor optical isolator by using Lamb equations, and found that the amount of optical isolation is 0.16 dB in an 80-µm-long (2.0 dB/mm) semiconductor optical isolator, where the directional coupler was designed so that 10% of light in the ring cavity is coupled to the output waveguide.…”
Section: Introductionmentioning
confidence: 99%